A great act of love : a novel - Rose, Heather, 1964- (Summit Books, 2026)
"Van Diemen's Land, 1839. A young woman of means arrives in Hobart, Australia, with a boy in her care. Leasing an old cottage next to an abandoned vineyard, Caroline Douglas must navigate an insular colony of exiles and opportunists and invent a new life on this island of extreme seasons and wild beauty. But Caroline is carrying a secret of such magnitude that it has led her to cross the world. It will take all she is made of to bring it into the light. A Great Act of Love is a spellbinding story that soars from the French Revolution to London and New York on an epic voyage to Tasmania. Here is a story of a family with champagne in their blood, and an enterprising woman determined to rewrite their legacy. The lives of Caroline, her father, and the residents of the island will collide in devastating and profound ways."--Amazon.